Digitizing observations from the Met Office Daily Weather Reports for 1900–1910 using citizen scientist volunteers. (4th June 2020) - Craig, Philip M.; Hawkins, Ed
Abstract: We describe the digitization of 1.8 million sub‐daily and daily weather observations which were recorded in the UK Met Office Daily Weather Reports during the 1900–1910 period. The data were rescued from scanned images of the original documents by 2, 148 volunteer citizen scientists using the weatherrescue.org website. The rescued observations include dry and wet bulb temperatures, daily maximum and minimum temperatures, daily rainfall amounts and sub‐daily sea‐level pressure from 72 different locations across western Europe. These observations will be used to fill gaps in existing pressure, temperature and rainfall records and are one of the largest recoveries of weather data by citizen scientists. The value of these additional observations is highlighted by comparing the pressure observations to the Twentieth Century Reanalysis version 3 ensemble for some specific case studies. Abstract : We have recovered 1.8 million observations of pressure, temperature and rainfall from the 1900–1910 Met Office Daily Weather Reports using citizen science volunteers. This dataset improves the spatial and temporal coverage of existing observational global and regional datasets of these variables. We show that the representation of extreme events in the 20th Century Reanalysis can be improved with the new pressure observations.